Rübsen-Dieselölmischung als Kraftstoff für Schlepper unter extremen klimatischen Bedingungen - Schäfer, Winfried (de, 1986)
Long term tests with vegetable oil fuels in Diesel engines are going on worldwide. Selection of vegetable oils used depends upon natural plant oil resources of the country, in which the tests are performed. This means, that also climatic conditions have effect on test results: both the quality of vegetable oil and the operating conditions for tractors depend upon climate.
Keywords: Ra; polttoaineet; rypsiöljy; kasviöljyt; dieselmoottorit; traktorit; turnip rape seed oil; tractor fuel; vegetable oil